SIFAT FISIKA KIMIA TANAH ORDO VERTISOL PADA PENGGUNAAN LAHAN PERTANIAN - Novita Anis Sholihah; Dwiyono Hari Utomo; Juarti Juarti (Jurnal Pendidikan Geografi, 2016)
Abstract: This research aims to know the physical and chemical properties of Ordo Vertisol soil in agriculture land used (paddy fields, dry fields, and farms). This research uses survey method that is implemented in the field and laboratory. Samples were obtained by overlaying two maps using Arc-GIS 10.1 software to produce the Land Unit Map, then the sample was taken by using purposive sampling method which consider the land was planted and has decreased of harvested area, or in productivity or the amount of crop production. Descriptive analysis is used to explain the results of the research and the discussion. The results showed that each land unit has high value of COLE and has properties that are supportive and unsupportive for the cultivation of plants, but each land unit has its differences. Land Unit 1A has the highest/fastest permeability because management is done more intensively, by constantly adding organic matter content that makes the soil density low. Land Unit 1B has higher organic matter because when taking the sample, there is still a part of crop residues and grasses on the surface than any other land units. The land management and irrigation also affect the content of organic matter in terms of its preservation. The lowest CEC contained in Land Unit 2 is caused by the content of the clay fraction is lower than other land units. Low organic matter content in Land Unit 2 also affect the low value of CEC, and the density becomes higher. The permeability in Land Unit 2 is also slower because of no management activities in this land. Land  Unit 3A has the lowest pH due to the given of ZA which produces Acid Sulphur on the land. Land Unit 3B have the highest CEC values for the content of the clay fraction is higher and the Montmorillonite mineral on this land has a per- manent charge. Organic materials in Land Unit 3B is also the lowest since the land is left empty before planted with soybeans.Keywords: ordo vertisol soil, land usage, land units